Analisis Penerapan Sistem Informasi Akuntansi Berbasis Komputer Menggunakan Microsoft Excel Terhadap Efektivitas Pengendalian Internal Sistem Penjualan - Eva Arifah; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2026)
This study aims to analyze the implementation of computer-based accounting information systems using Microsoft Excel and its impact on the effectiveness of internal control in sales systems. The research adopts a non-empirical approach using a Systematic Literature Review (SLR) method to synthesize findings from relevant academic sources. The analysis reveals that Microsoft Excel improves the structure, accuracy, and timeliness of transaction recording, thereby supporting more reliable financial information for managerial decision-making. However, the flexibility of spreadsheet-based systems introduces inherent risks, including input errors, data manipulation, and limited audit trails, which may weaken control effectiveness if not properly managed. The findings indicate that the successful implementation of such systems depends on technological utilization, organizational governance, standardized system design, and user competency, while also contributing to a conceptual framework that emphasizes alignment between technology, internal control, and organizational capacity in achieving sustainable sales system management.